Phenotypic Characteristics of Local Pigs in the North Sulawesi - Jane S. I. T. Onibala; Suyadi Suyadi; Sucik Maylinda; V. M. A. Nurgiartiningsih (Fakultas Peternakan, Universitas Padjadjaran, 2022)
Local pigs are one of Indonesia's livestock germplasm and have an important role in the rural farming system in the North Sulawesi. The aim of this study was to identify the phenotypic characteristic of local pigs in the North Sulawesi. The study was carried out as a field level survey and investigation through direct observation of phenotypic traits of local pigs in eight villages which is located in the two main regions of the North Sulawesi, namely Minahasa Utara (Darunu, Sonsilo, Marinsow and Kalinaun) and Bolaang Mongondow (Pindolili, Baturapa, Sangtombolang and Tanjung Sidupa). A total of 212 pigs were used to observe the parameters of body weight, body length, heart grith, height at withers, head length and ear length. Data were analyzed using general linear model and discriminant analysis. The results showed that body weight and linear body measurement of local pigs in eight locations in the North Sulawesi were significantly different (p < 0.05) with the following traits; average body weight of 27.67±12.90 kg, body length of 70.62±14.21 cm, heart grith of 62.89±13.30 cm, height at withers of 44.73±8.86 cm, head length of 25.06 ±5.96 cm, ear length of 15.6±4.05 cm and hock circumference of 9.87±1.31 cm.